Evaluation of the Tuesday Literacy Program (LISA) at SDN 5 Sekotong Tengah Using the CIPP Model - Nuraeni (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to evaluate the implementation of the Tuesday Literacy Program (LISA) at SDN 5 Sekotong Tengah using the CIPP evaluation model (Context, Input, Process, Product). An evaluative research approach was adopted through a descriptive qualitative design supported by quantitative data. The participants comprised the school principal, teachers, and students involved in the program. Data were collected through observations, semi-structured interviews, documentation review, and literacy tests. The findings revealed that, from a contextual perspective, the program was relevant to the school’s needs and aligned with national literacy policies. In terms of input, human resources were generally adequate, although the availability of reading materials remained limited. Regarding the process, the program was implemented systematically; however, student participation was not evenly distributed. The product evaluation demonstrated an average improvement of approximately 15% in students’ literacy skills, while a proportion of students continued to perform below the minimum competency standard. Overall, the LISA Program proved effective in strengthening literacy culture in elementary schools, although further improvements are required in learning resources, parental involvement, and continuous monitoring to enhance program sustainability.